Design and Development to Face Recognition System by Synthesizing AADHAR Enabled Platform for Online Voting (International Journal of Innovative Research in Computer Science & Technology, 2020)
It’s a web based named as “online voting  system” which aims to develop a computerized system to  make the election process more secure and user friendly.  This system has many features which are generally not  available in current days. With the help of this system,  user can cast their vote without going to any polling  booth; it can save their time and effort. This system can  also save money of government which is spent in  preparation of election process. This system uses face  detection and recognition technology to make this system  more secure and safe. Overall this project of ours is being  developed to help staff of Election commission of India  and also reduce the human efforts.
Keywords: Online voting; Biometric authentication; Security system